The abstraction habituation model of knowledge worker burnout - Meaden, James (Frontiers in Psychology, 2026)
Burnout among knowledge workers presents a puzzle: many workers report persistent burnout despite relatively favorable conditions, and interventions show limited lasting effects. Dominant resource models assume rest restores function, yet cannot fully explain why recovery fails despite adequate time, why burnout remains stable despite accumulating resources, or why mindfulness intervention effects fade when practice stops. Building on the environmental model of mindfulness, this paper introduces abstraction habituation: the progressive loss of cognitive flexibility through sustained knowledge work. The model proposes that neuroplastic adaptation establishes abstraction as the default processing mode, reducing the concrete processing capacity that supports psychological recovery. This framework accounts for career-long burnout stability and limited intervention durability through cumulative cognitive training, suggesting effective prevention requires redesigning work environments to preserve cognitive flexibility, not solely adding individual coping resources.